Mercurial Contamination: A Consumer Health Risk Assessment Concerning Seafood From a Eutrophic Estuary in Southeastern Brazil - Rodrigues, Paloma de Almeida; Ferrari, Rafaela Gomes; Rosário, Denes Kaic Alves do; Hauser-Davis, Rachel Ann; Santos, Luciano Neves dos; Conte-Junior, Carlos Adam (Frontiers in Marine Science, 2022)
Mercury (Hg) contamination has increased in the last decades, resulting in human consumption concerns mainly in developing countries. In this context, this study aimed to carry out a health risk assessment regarding the consumption of swimming crabs, shrimp and squid species caught in different regions of the Guanabara Bay, Rio de Janeiro, Brazil. For this purpose, we used calculations that indicated the Estimated Monthly Intake (EMI), Maximum Monthly Intake Rate (IRmm) and Hazard Quotient (HQ). As the target population, the mean weight corresponding to men and women children aged 12 years, young people aged 24 years, and middle-aged people (adults) aged 54 years were used, taking into account the female and male gender. In the studied seafood, the EMI (0.0001 to 0.0006 mg.kg.month-1) was below the monthly intake limit and IRmm (10.3 to 34.8 kg month-1) indicates that large quantities of seafood can be consumed by the population studied, unless the safe limit of monthly intake of the contaminant is reached. The hazard quotient (0.4 to 1.4) indicate potential risks health of children eating swimming crabs and squid and young women eating swimming crabs. Our study also highlights the importance of risk assessments, as even when seafood contains Hg concentrations below established limits, consumption variables must be taken into account, so as not to underestimate the potential health risks.